POLITIK HUKUM EKSEKUSI PUTUSAN PENGADILAN TATA USAHA NEGARA - MEITA LEFI KURNIA, DOLA RIZA dan (Normative Jurnal Ilmiah Hukum, 2025)
The problem of implementing the decision of the State Administrative Court is that the mechanism for how the decision must be implemented in accordance with the expectations of seekers of legal justice in Indonesia has not been found. The type of research conducted is normative research. The writing of this scientific paper uses primary, secondary and tertiary legal sources. The problem of this legal research is how is the legal policy of executing the decision of the State Administrative Court? The conclusion of this paper is that the legal policy of executing the decision of the State Administrative Court can be carried out by forming a new law or by replacing the old law. With the many weaknesses in the current applicable law and the absence of implementing regulations to overcome the weaknesses of the existing law, the legal policy that can be carried out is to form government regulations on the mechanism and procedures for executing the decision of the State Administrative Court.